2016
DOI: 10.1099/mic.0.000257
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of monomeric transcriptional regulators in Mycobacterium tuberculosis

Abstract: Gene transcription catalysed by RNA polymerase is regulated by transcriptional regulators, which play central roles in the control of gene transcription in both eukaryotes and prokaryotes. In regulating gene transcription, many regulators form dimers that bind to DNA with repeated motifs. However, some regulators function as monomers, but their mechanisms of gene expression control are largely uncharacterized. Here we systematically characterized monomeric versus dimeric regulators in the tuberculosis causativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…A survey of the monomeric transcription regulators of M . tuberculosis showed that WhiB1 interacted with the major sigma factor, σ A 33 . Aerobic purification of an N-terminally His-tagged M .…”
Section: Resultsmentioning
confidence: 99%
“…A survey of the monomeric transcription regulators of M . tuberculosis showed that WhiB1 interacted with the major sigma factor, σ A 33 . Aerobic purification of an N-terminally His-tagged M .…”
Section: Resultsmentioning
confidence: 99%
“…63 However, in our hands FeoC appears to remain monomeric in the presence of its cluster, which is unusual although not unheard of for transcriptional regulators. 64, 65 Alternatively, FeoC could function as part of the larger Feo complex, which could be dynamic under changing cellular conditions in cooperation with FeoB. Support that FeoC is part of the larger complex is found in the Kp NFeoB- Kp FeoC co-crystal structure (although the [Fe-S] cluster is absent) 66 , and in studies on V. cholerae Feo system, that have shown that FeoA/B/C interact 25, 67 (although Vc FeoC is one of only a handful of FeoCs that lack the necessary cluster-binding residues).…”
Section: Discussionmentioning
confidence: 99%
“…Lowest-energy NMR conformer of Ec FeoC (PDB ID 1XN7). Labeled regions are: the helix-turn-helix (HTH) motif and the unstructured wing region that contains four Cys residues (Cys 56 , Cys 61 , Cys 64 and Cys 70 ) involved in [Fe-S] cluster binding. The labels “N” and “C” represent the amino and carboxy termini, respectively.…”
Section: Figurementioning
confidence: 99%
“…A general conclusion from previous characterizations of Wbl proteins is that they are monomeric proteins ( 2 , 12 , 28 ), and so these findings for Sv WhiD were unexpected. We note that Sv WhiD has a C-terminal extension of 18 residues compared with Sc WhiD, and, although the proteins exhibit overall 78% sequence identity, only 1 of the last 33 residues of Sv WhiD is conserved in Sc WhiD (the proteins are 100% identical from residues 1–95) ( Fig.…”
Section: Resultsmentioning
confidence: 84%